Biochemical mediators during active and retentive phases of tooth movement in orthodontic patients—a scoping review - Ananthanarayanan, Venkateswaran; Padmanabhan, Sridevi (Frontiers in Oral Health, 2025)
IntroductionCrowding or spacing of teeth will impair oral hygiene maintenance and therefore lead to poor oral health and nutrition. Orthodontic treatment aligns the teeth and establish a proper occlusion, both of which are essential in the integrity of oral health and nutrition. Despite advancements in orthodontic treatment, relapse (teeth returning to the previous position) remains a major challenge. Previously, collagen turnover was considered the main factor, but aligns studies suggested extracellular matrix proteins such as tyrosine protein kinase (TEC protein) play a more significant role due to their exclusive presence during the retention phase. While extensive research exists on OTM, few studies have explored biochemical mediators during retention. The primary objective of this scoping review is to identify biochemical mediators at different timelines during OTM and relapse to consolidate findings and address gaps so that orthodontists may attempt to alter the mediators thereby restoring oral health and nutrition.MethodThis scoping review complied with the PRISMA-ScR guidelines. The search terms used were MESH terms and Boolean terminology. The search was conducted until July 2023 across five databases; PubMed, Scopus, Medline, Embase, and Google Scholar, including gray literature and unpublished data. The resulting numbers of articles (120) were chosen for the scoping review after matching with the framed inclusion and exclusion criteria (distributed as 113 and 7 studies for active and retentive phases respectively). Each reviewer stored the retrieved list of articles in separate folders designated for each database. The two reviewers resolved discrepancies through discussion. Any points of disagreement or conflict in the conducted search were escalated to the third senior reviewer, whose judgment was final.ResultsThe extraction of relevant data was independently performed by the two reviewers. The following data were analyzed: author name, journal, year of publication, type of study, sample size, sample site, type of biomarker assessed, and stage of orthodontic treatment. Queries pertaining to a particular study were clarified by contacting the lead author. The data were compiled individually by each reviewer into a draft chart and then discussed to reach a consensus. These data were then shared with a third senior reviewer to streamline and finalize the data.ConclusionsThe literature on biomarkers of tooth movement is exhaustive. However, studies on biomarkers during the retention phase are limited, and more exploration is needed.Systematic Review Registrationhttps://osf.io/sh6u5.